A proteção previdenciária à gestante exposta a riscos à saúde no ambiente de trabalho - Láua, Carolina Alves Corrêa (2023)
This dissertation addresses the legal changes related to the protection of working women, focusing on the gestation period, especially with regards to the environmental risks to which they may be exposed to during the working day, and, especially, with the advent the COVID-19 pandemic. The problem arises with the enactment Laws n. 13.287/2016 and n. 13.467/2017, that amended the Consolidation of Labor Laws, as well as Laws n. 14.151/2021 and n. 14.331/2022, which deal with the removal of pregnant women from face-to-face work during the pandemic. This work addresses labor protection, and in the ways in which it can occur, as well as social security protection. Demonstrates that the protection for pregnant women can be jointly implemented by social security law and labor law, however, we try to clarify that the social security protection for pregnant women exposed to harmful agents offered by the Labor Reform was erroneously implemented. In addition, it shows that the absence of a legal provision that would protect pregnant women on leave during the pandemic, and who were unable to perform their duties remotely, generated uncertainty about how the pregnant woman should be protected. From this context, it is intended to analyze and demonstrate the legal possibility of social security to protect pregnant workers exposed to health risks in the work environment and how this protection should be implemented